2003
DOI: 10.2166/wh.2003.0021
|View full text |Cite
|
Sign up to set email alerts
|

Use of viral pathogens and indicators to differentiate between human and non-human fecal contamination in a microbial source tracking comparison study

Abstract: Assays for the detection and typing of adenoviruses, enteroviruses and F+ specific coliphages were performed on samples created as part of a national microbial source tracking methods comparison study. The samples were created blind to the researchers, and were inoculated with a variety of types of fecal contamination source (human, sewage, dog, seagull and cow) and mixtures of sources. Viral tracer and pathogen assays demonstrated a general ability to discriminate human from non-human fecal contamination. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 29 publications
2
75
0
2
Order By: Relevance
“…PCR viral detection is less laborious and time-consuming and also more specific and sensitive than cell culture (Table 2) (27,66,79). Results from PCR assays can be obtained within 24 h of sampling, compared to days or weeks of incubation for cell culture assay (62,120). PCR is also capable of differentiating specific viruses (79,86,127).…”
Section: Virus Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR viral detection is less laborious and time-consuming and also more specific and sensitive than cell culture (Table 2) (27,66,79). Results from PCR assays can be obtained within 24 h of sampling, compared to days or weeks of incubation for cell culture assay (62,120). PCR is also capable of differentiating specific viruses (79,86,127).…”
Section: Virus Detection Methodsmentioning
confidence: 99%
“…However, the cost of a real-time PCR instrument is still substantially more than that of a conventional PCR instrument, and in some cases, real-time PCR has been shown to be less sensitive than conventional RT-PCR and nested PCR (120). Noble et al (120) reported that human adenovirus 40 was detected by real-time PCR in only two of the four samples positive for adenoviruses by conventional nested PCR; none of the samples that were positive for enteroviruses by conventional RT-PCR was detected by real-time RT-PCR.…”
Section: Virus Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, non-enveloped viruses are more resistant to decontamination processes used in both drinking and wastewater treatments as well as being more species-specifical than bacteria, which may indicate them as candidates for microbial source tracking (Noble et al, 2003;. Therefore, the analysis of viruses in conjunction with bacteria may be advantageous for detection and identification of sources for fecal contamination.…”
Section: Introductionmentioning
confidence: 99%
“…ing applications (Jofre et al, 2011;Noble et al, 2003;Scott et al, 2002). GI and GIV have been found predominantly associated with animal feces and GII and GIII in human sources of fecal contamination (Osawa et al, 1981;Schaper et al, 2002).…”
Section: Introductionmentioning
confidence: 99%